The effect of Salam Leaves Extract (Syzygium Polyanthum Wight.) on Urine Volume in The Potassium Oxonic-Induced Hyperuricemia Mice - Muhtadi Muhtadi (Universitas Muhammadiyah Surakarta, 2019)
This study aims to determine how Salam (Syzygium polyanthum Wight.) leaves extracts affect the urine volume of potassium oxonic-induced mice. Fifteen Swiss male mice were divided into 3 groups. Group I (normal group) were given intraperitoneal aquadest 1 mL/20g.bw, group II (negative group) and group III (Salam leaves extracts group) were given intraperitoneal 250 mg/kg.bw of potassium oxonic. After 1 hour of the treatment, group I and group II were given aquadest 0.5 mL/20g.bw orally, while group III was given Salam leaves extracts 200 mg/kg.bw orally. Mice are included in metabolic cage. The cumulative urine volume data were analyzed by Kruskal-Wallis and and Mann-Whitney test with a confidence level of 95%. In the urine volume profile test, the negative group did not experience a significant increase in urine volume when compared with the Salam leaves extracts group at hyperuricemia for 3 days (p 0.05), while the negative group had higher urine volume when compared to the normal group (p = 0.007). The results of this study indicated that Salam leaves extracts were not able to increase urine volume in hyperuricemic conditions.